Extending epistemology for programme evaluation – can After Action Rev iews become spaces for critical reflection? - Apgar, Marina; Snijder, Mieke (2020)
The term After Action Review (AAR) is becoming more common in the worl d of development evaluation, particularly in programmes that focus on evaluation as a formative learning process. As structured and facilita ted learning moments, AARs take many shapes always built to support a specific team in a specific moment on their journey. Across such a div ersity of practice how do we understand the evolution of the AAR as a method with an action research orientation? Being mindful always of th e risk of instrumentalising and co-opting participatory methods, there is danger that AARs become an empty programme ritual, remaining at th e surface and failing to achieve critical reflection and so falling sh ort of their intention of pushing for deeper change in our practice. A s the evaluation and learning team of two large complex, multi-partner projects using research to address development challenges, we have be en applying the AAR method while adapting to virtual COVID working wit h partners across the world. As action researchers we have been thinki ng about what critical reflection means within a programme AAR process and whether and how they can open up a second person inquiry space.